PENGARUH REKRUTMEN DAN KOMUNIKASI TERHADAP PRODUKTIVITAS KERJA APARATUR SIPIL NEGARA DEPARTEMEN SATUAN MARKAS RUMAH SAKIT ANGKATAN LAUT DOKTER MINTOHARDJO JAKARTA PUSAT - Agnes Velisa Simatupang; Shela Indah Savitri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine the partial and simultaneous effects of recruitment and communication on the work productivity of State Civil Apparatus personnel in the Headquarters Unit Department of Dr. Mintohardjo Naval Hospital, Central Jakarta. The study used a descriptive quantitative approach. The population consisted of 64 employees, all of whom were selected as respondents through saturated sampling. Data were collected using questionnaires and analyzed with SPSS version 26 through validity and reliability tests, classical assumption tests, simple and multiple linear regression, correlation, coefficient of determination, t-tests, and an F-test. Recruitment had a positive and significant effect on work productivity with the equation Y = 11.269 + 0.666X, r = 0.781, R² = 0.610, and t = 9.854 (p < 0.001). Communication also had a positive and significant effect with the equation Y = 5.871 + 0.820X, r = 0.807, R² = 0.652, and t = 10.766 (p < 0.001). Simultaneously, recruitment and communication significantly affected work productivity with the equation Y = 4.166 + 0.360X1 + 0.518X2, R = 0.861, R² = 0.741, and F = 87.186 (p < 0.001). These findings indicate that a more appropriate recruitment process and effective organizational communication can improve employee productivity.